2020
DOI: 10.1136/bmjopen-2020-039274
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise on symptoms of premenstrual syndrome in low and middle-income countries: a protocol for systematic review and meta-analysis

Abstract: IntroductionPremenstrual syndrome (PMS) has the potential to affect the quality of life adversely. Published guidelines recommend the use of exercise as part of the first-line management interventions for PMS. However, the published evidence related to the effectiveness of physical activity and PMS is inconclusive. This review will assess the effectiveness of exercise-based interventions in reducing PMS in women screened or diagnosed with PMS in low and middle-income countries, where the prevalence of PMS is h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Globally, over 90% women of reproductive age experience at least one symptom of PMS (Badkur et al, 2016; Matsumoto et al, 2021), with a high prevalence in low and middle‐income countries. For example, in nearly half of the (49.6%) adolescent populations reportedly experience PMS (Dutta & Sharma, 2021; Pokharel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, over 90% women of reproductive age experience at least one symptom of PMS (Badkur et al, 2016; Matsumoto et al, 2021), with a high prevalence in low and middle‐income countries. For example, in nearly half of the (49.6%) adolescent populations reportedly experience PMS (Dutta & Sharma, 2021; Pokharel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The elevated premenstrual pelvic blood flow along with exercising delayed the onset of pain. During menstrual pain, exercising can result in faster transfer of wastes and prostaglandins from the uterus, which are the main cause of menstrual pain, from the uterus (19). Harlow and Park, Blakey et al reported that there was no relationship between exercise and primary dysmenorrhea (20).…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin insufficiency and increased sensitivity to progesterone can also be responsible for the disorder. The occurrence and increase in severity of PMS symptoms can be caused by neurohormonal and genetic factors that are still researched along with mineral and vitamin deficiency, and unhealthy lifestyle (Pokharel, Rana, Moutchia, Uchai, Kerri, Gutiérrez, Islam, 2020).…”
Section: Introductionmentioning
confidence: 99%